The sector of social joint economy and entrepreneurship and its contribution to the growth of the Region of East Macedonia-Thrace (REMTH). - Banteka, Eleftheria; Stathakis, Efthimios; Daltagianni, Dimitra (International Journal of Scientific Research and Management (IJSRM), 2025)
In this paper we dealt with the social economy/ entrepreneurship and we showed that it has significant impact for development in Greece and the Region of East Macedonia and Thrace (REMTH). We empirically found that this business model suits the Greek regions and especially in REMTH, which is transforming gradually its economy, offering smart innovative ideas and jobs. The social economy introduces the idea of ​​entrepreneurship to people who would not otherwise dare to take a business venture. They are flexible, motivated, put forward in a series of public procedures and have many competitive advantages. They give outlet to collaborative and synergetic creativity and support open innovation. They produce jobs, distribute income to the many, protect the weakest in the business and production chain from the most powerful competitors. They fight speculation, exclusion, poverty and serve the family, social solidarity, cohesion and other public goals. In the context of the work, we highlighted how social enterprises are created, operated, who can participate in them and how through their smart business opportunities empower and develop the  local communities. We also highlighted that the institution of solidarity economy bodies is suitable for serving the goals of inclusion, integration and combating exclusion. We concluded that, the more social economy and enterprises, the more support to the collective effort for the development of REMTH.